Quality of Acid-Preserved Edamame Soybean at Immature and Mature Stages - Moseley, David; Mozzoni, Leandro; Orazaly, Moldir; Florez-Palacios, Liliana; Chen, Pengyin (Frontiers in Sustainable Food Systems, 2020)
Edamame is a food-grade soybean that is harvested at the green-immature stage (R6) and sold fresh or frozen for consumption after steaming or boiling. Limited studies have been conducted on high-temperature sterilization of edamame in cans and on acid preservation of edamame. The objectives of this study were to evaluate the color retention and texture of edamame when pasteurized in acidic brine as compared to boiling, to assess the effect of sucrose and turmeric addition on acid-treated edamame, and to characterize varietal differences when edamame lines were pasteurized in an acidic brine at either R6 or R8 stage. All studies were conducted using industry-standard processing conditions for acid-preservation of food in glass containers. The results of this research indicated that acid processing caused losses in intensity of green color and hue, but much smaller than those reported when heat-processing edamame in cans. We also observed a small and borderline significant increase in texture (p = 0.0790) in acid-preserved samples. In addition, we found that green color is positively affected by the addition of turmeric to the brine, but not of sucrose. Finally, the varieties R07-589 (red-brown seed coat) and R09-345 (black seed coat) acid-processed at R8 had color and texture similar to canned in-kind substitute products. In conclusion, acid-preservation, and addition of turmeric to immature edamame, helped maintain an acceptable quality of the processed products.